Optimalisasi Promosi Kepariwisataan Melalui Digital Marketing: Pemberdayaan Pokdarwis di Kampoeng Kita Setu, Kabupaten Bekasi - Akhmad Wahidin; Yudhistira Wirya Saputra; Tatik Yuniarti (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The advancement of digital technology has revolutionized the way tourism destinations are promoted, particularly by local communities. This article presents the results of a community service program conducted by graduate students of the Master of Communication Science at Universitas Paramadina, Cikarang Campus, focusing on optimizing tourism promotion through digital marketing in Kampoeng Kita Setu, Bekasi Regency. The program aimed to empower local Tourism Awareness Groups (Pokdarwis) through a series of activities such as seminars, workshops, the launch of a digital tourism map, digital content creation training, and the signing of an Implementation Agreement. The primary objective was to enhance the capacity of Pokdarwis in utilizing social media as an effective and sustainable promotional tool. Collaboration among community members, academics, and local government emerged as a key factor in developing community-based tourism. The program outcomes indicate a significant improvement in digital literacy among Pokdarwis members and a growing commitment to independently and professionally manage destination promotion.